Breakfast of Champions: Towards Zero-Copy Serialization with NIC Scatter-Gather - DeeptiRaghavan; Levis, Philip; Zaharia, Matei; Zhang, Irene (Hot Topics in Operating Systems, 2021)
Microsecond I/O will make data serialization a major bottleneck for datacenter applications. Serialization is fundamentally about data movement: serialization libraries coalesce and flatten in-memory data structures into a single transmittable buffer. CPU-based serialization approaches will hit a performance limit due to data movement overheads and be unable to keep up with modern networks. We observe that widely deployed NICs possess scatter-gather capabilities that can be re-purposed to accelerate serialization's core task of coalescing and flattening in-memory data structures. It is possible to build a completely zero-copy, zero-allocation serialization library with commodity NICs. Doing so introduces many research challenges, including using the hardware capabilities efficiently for a wide variety of non-uniform data structures, making application memory available for zero-copy I/O, and ensuring memory safety.